Scheduling of irrigation for sugarcane (Saccharum officinarum) - GUPTA, RAJENDRA; TRIPATHI, S K (The Indian Journal of Agricultural Sciences, 2013)
Irrigation schedules developed basis of on the mean weather data of 30 years from 1965-95 for predominentsugarcane (Saccharum officinarum L.) growing locations of India indicate that the highest number of irrigations(20) and amount of water (2 643 mm) are required at Ganganagar and Rajkot respectively, whereas lowestnumber of irrigations (3) and amount of water (303 mm) are required at Cochin. Highest water-use efficiencyof 2 221 kg/ha-cm has been observed at Cochin and the lowest (175 kg/ha-cm) at Indore. For highersugarcane yield and sugar recovery, the optimum share of sugarcane in net irrigated area of the state wasfound to be 15%.